Pengaruh Campuran Fasad Bangunan Arsitektur Eropa Dan Lokal Terhadap Tampilan Bangunan - Kurniawan, Agung; R Sukardi, Rahy; Rahaya, Pistiani (Jurnal Syntax Fusion, 2024)
The BJB Syariah Building is a Colonial Building with a European Architectural style, this building combine European and local elements, the façade of this building really reflects the European style. This research focuses on the mixture of local and European culture seen through buildings such as BJB Syariah Bandung which is the result of a combination of European and Indonesian architectural style. The type of research used in this study is qualitative research. Because this research uses a qualitative approach, the data results will be focused in the form of descriptive statements and do not review a hypothesis and do not correct variables. The result of his research is the composition of the façade that considers functional elements such as windows, doors, sun protection, and roof planes, as well as the emphasis on creating harmonious unity through good proportions, vertical and horizontal structures, rhythm of materials, colors, and decorative elements being the focal point.